Bismuth based novel substrate for surface enhanced Raman spectroscopy - Saroj A.; Sharma U.; Das S.; Ramanathan V. (My University, 2025)
Exploring the potential of non-noble metal substrates for Surface-enhanced Raman spectroscopy (SERS) has attracted considerable interest in recent years. In this work, we prepared nanoplate β-Bi2O3/Bi2O2CO3 heterostructure via calcination of Bi2O2CO3 precursor using a facile hydrothermal process and successfully demonstrated its use as a novel SERS substrate. The SERS sensitivity of substrate was performed by probing methyl orange (MO), rhodamine B (RhB), vitamin C (Vit. C), and melamine. The observed results show that the SERS signal is enhanced considerably by the adsorption of probe molecules on the surface of the Bismuth heterostructure SERS substrate. © 2022 Elsevier B.V.